DIGITALISASI CERITA RAKYAT PUTRI HIJAU MELAYU DELI YANG HAMPIR PUNAH: KAJIAN SASTRA DIGITAL - Gibran Srg, M. Khalil; Chairunisa, Hera (Asosiasi dosen IDEBAHASA KEPRI, 2022)
This research aims to save one example of cultural heritage, namely the folklore of the Green Princess of Deli Malays through digitalization in the form of digital comics. The methods used in this study include literature studies, data collection, analysis of story structure and cultural values, and the creation of digital comics by paying attention to literary elements and cultural authenticity. The expected results of this study are to contribute to the preservation and redistribution of the folklore of the Green Princess of Deli Malays. By producing interesting and quality digital comics, it is hoped that it can attract the interest of the younger generation to learn and appreciate local cultural heritage. Furthermore, this study will also show the potential of digital technology in preserving culture and encouraging digital literary creativity. This research is important in strengthening local cultural identity, increasing cultural literacy of the younger generation, and maintaining the sustainability of cultural heritage for the future.